Analysis of psychological evaluations in academies of football elite - Ródenas, L.; Medina-Villanueva, S.; Vanegas-Farfano, M.; Espino, F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
The use of science and technology applied to sports demands the investigation of effective methods and techniques that allow the increasingly necessary improvement of sports training and the inclusion and participation of the psychologist as a permanent demand and tool in team sports. Today the tactical preparation, its control and evaluation form in the sports training process is recognized as the first step to develop and improve in teams of 1st category in Mexico and the world, as well as the psychological preparation, imbued within the tactical preparation, that is why the great sports potencies in the world are currently striving to optimize this important process of preparing the athlete. Sports psychology has developed and consolidated its presence in the entire field of competitive sports practice. This science acts in the individual and group aspect, teaching the athlete to eliminate negative thoughts or to use concentration techniques, in addition to making the smartest decision at the most suitable moment. Sports Psychology nourishes from the sources of Social Psychology for the necessary explanation of these phenomena considering the background and development of social thinking (Predvechni and Sherkovin, 1986). Method The evaluation consisted in the application of a battery of psychological variables tests, which were applied in January and April 2019 to four categories of the Football Club. 11 psychological constructs were evaluated in total, its descriptive statistics were calculated according to category (U20 - U17 - U15 - II) and the moment of application (T1 and T2). Likewise, the changes in the psychological variables were analyzed according to the moment of application, the prediction of burnout and satisfaction with the life of T2 was analyzed based on the interpersonal styles of the coach generated in T1. Results and Discussion According to the results of the study both in the comparisons by variables, times (T1 and T2) and categories, it is important to act in a brief form in the sub-20 and second division categories, since they are at risk of truncating an adequate integral development of the soccer player, predicting a burnout and few intentions to continue with a physically active life as soon as he concludes his stage as professional soccer player.